2021
DOI: 10.1002/ppul.25679
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profile in Egyptian children and adolescents with COVID‐19 pneumonia: A multicenter study

Abstract: Background: To date, the cytokine profile in children and adolescent with novel coronavirus disease 2019 (COVID-19) has not been reported. Objectives:We investigated serum levels of a panel of key cytokines in children and adolescent with COVID-19 pneumonia with a primary focus on "cytokine storm" cytokines such as interleukin (IL)-1β, IL-6, IL-17, IL-2, IL-4, IL-10, interferon (IFN-γ), tumor necrosis factor (TNF)-α, and two chemokines interferon-inducible protein-10 (IP-10) and IL-8. We also studied whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 42 publications
3
16
0
Order By: Relevance
“…The findings of inflammatory marker elevation in plasma corroborate results from other studies reporting a strong increment of pro-inflammatory cytokines in adults as well as in the few paediatric studies that exists to date (17,(26)(27)(28)(29). However, a striking feature of the present study is the lack of differences regarding cytokines that have been implicated as markers of disease severity, most notably IL-6 and IL-10 (30,31).…”
Section: Discussionsupporting
confidence: 91%
“…The findings of inflammatory marker elevation in plasma corroborate results from other studies reporting a strong increment of pro-inflammatory cytokines in adults as well as in the few paediatric studies that exists to date (17,(26)(27)(28)(29). However, a striking feature of the present study is the lack of differences regarding cytokines that have been implicated as markers of disease severity, most notably IL-6 and IL-10 (30,31).…”
Section: Discussionsupporting
confidence: 91%
“…21 A multicenter study demonstrated that for children with severe COVID-19, IL-1β, IL-6, and chemokine interferon-inducible protein-10 were dramatically increased, which could independently predict severe pneumonia in children with COVID-19. 22 In consistence with the above results, IL-6, IL-1β, and TNF-α were significantly upregulated in LPStreated WI-38 cells, but knockdown of EPSTI1 obviously suppressed inflammatory responses, indicating that IL-6, IL-1β, and TNF-α contributed to the inflammatory responses while inhibiting EPSTI1 alleviated LPS-caused inflammation.…”
Section: Discussionsupporting
confidence: 66%
“…This agreed with findings of previous studies. 18,19,20 In contrary, a study by Burgos-Blasco et al, 2020, did not find a difference between COVID-19 patients and control subjects. 21 In the current study, by analyzing the mean IL-17 serum levels among the moderate and severe cases, we observed that although the mean serum titers of IL-17 were higher in the severe group compared to the moderate group, but the difference did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 86%